RETRACTED: Improving the process of training specialists on the introduction of innovative technologies - Ivanov Igor; Persiyanova Galina (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001